Different Heat Shock Proteins Bind α-Synuclein With Distinct Mechanisms and Synergistically Prevent Its Amyloid Aggregation - Jia, Chunyu; Ma, Xiaojuan; Liu, Zhenying; Gu, Jinge; Zhang, Xiang; Li, Dan; Zhang, Shengnan (Frontiers in Neuroscience, 2019)
α-Synuclein (α-Syn) forms pathological amyloid aggregates deposited in Lewy bodies and Lewy neurites in the brain of Parkinson’s disease (PD) patients. Heat shock proteins (Hsps) are the major components of the cellular chaperone network, which are responsible for preventing proteins from amyloid aggregation. Different Hsps were reported to interact with α-syn. However, the underlying mechanism of the interplay between α-syn and different Hsps remains unclear. Here, by combing NMR spectroscopy, electron microscope and other biochemical approaches, we systemically investigated the interaction between α-syn and three Hsps from different families including Hsp27, HDJ1 and Hsp104. We found that all three Hsps can weakly bind α-syn and inhibit it from amyloid aggregation. Intriguingly, different Hsps recognize distinct regions of α-syn monomer, and act synergistically in chaperoning α-syn from fibril formation in sub-stoichiometry. Our results revealed the diverse binding mechanisms employed by different Hsps to tackle α-syn, and suggested that different Hsps form a network for cooperatively chaperoning α-syn from pathological aggregation.